The Impacts of Supply Chain Relational Benefit on Inter-organizational Knowledge Sharing: Cross Validation of SEM - 劉文良; Wen-Liang Liu (My University, 2010)
過去有關知識分享的研究主題，大多主要在探討企業內之知識分享。由於供應鏈管理思維的興起，研究主題近年來漸漸移向組織間或供應鏈間之知識分享。雖然已有學者注意到供應鏈組織閉關條對供應鏈組織間知識分享有所影響，但卻很少有學者從關係利益的角度來看組織間知識分享的社會交換行為，更缺乏對其中重要中介因素的瞭解，例如，關係承諾與信賴。為此，本研究從社會交換理論的觀點，以台灣製造業為研究對象，並加入信賴與承諾二項中介影響因素，深入探討供應鏈關係利益對組織間知識分享意願與分享行為之影響。實證結果發現，供應鏈組織閉關係利益中的信心利益會透過中介變數－關係承諾與信賴，影響知識分享意願。而中介變數中的信賴也會影響關係承諾。此外，本研究亦檢定跨期的交叉效度以確認本研究結果並非來自於單期的特殊現象。

The literature of knowledge sharing in the past most1y focused on the internal organization. However, new thinking of supply chain management gradually focused on knowledge sharing within the supply chain. Although scholars have noticed that supply chain relationships int1uence knowledge sharing of the supply chain, few scholars have examined knowledge sharing of supply chain in terms of relationship benefits and its intervening variables such as commitment and trust. Using Taiwanese manufacturing companies as the research subjects, this research examines the int1uence of relationship benefits as well as commitment and trust on supply chain knowledge sharing. This research shows that: (1) the relationship benefits of supply chain int1uence supply chain knowledge sharing, (2) commitment and trust mediate the relationship between relationship benefit and knowledge sharing. The results were cross-validated. Commitment and trust thus play key roles in companies' willingness to share knowledge with their suppliers.
供應鏈關係利益對組織間知識分享之影響－Sem交叉效度檢定
Keywords: 關係利益; 知識分享; 供應鏈; 社會交換理論; Relational Benefit; Knowledge Sharing; Supply Chain; Social Exchange Theory